Coagulation: flocculation and performance evaluation of Hylocereus undatus (white dragon fruit) foliage as a natural coagulant for paint wastewater treatment / Aina Afiqah Ramlee - Ramlee, Aina Afiqah (2023)
Towards exploring the application of natural coagulants in industrial wastewater treatment, plant-based coagulants have been gaining more interests due to its potentials such as biodegradability and easy availability. Hylocereus undatus foliage as the plant based coagulant has been proven to be efficient during the coagulation – flocculation process; however, limited research has been reported focusing only on palm oil mill effluent (POME) and latex concentrate wastewater. In addition, limited study has been carried out to determine the performance evaluation of H.undatus foliage in treating different types of wastewaters incorporating different operating conditions using optimization techniques. Hence, this study employed response surface methodology(RSM) in an attempt to determine the performance evaluation of the coagulant in paint waste water treatment, its characterization, and the mechanism that prompts the coagulation - flocculation process. The standard jar test method was utilized in investigating the effect of pH value, coagulant dosage, rapid mixing speed and temperature as the operating conditions on turbidity, chemical oxygen demand (COD)and suspended solids (SS).